The Role of Law in Enforcing Peace Agreements: Lessons Learned from Colombia. (17th January 2021) - Müller, C Sophia
Abstract: Peace agreements are frequently violated. These violations can result in the resumption of armed conflict. Yet, while there is an entire body of political science literature on the factors that influence the success or failure of peace agreements, there are only few legal scholars who deal with the implementation and enforcement of peace agreements. Law has the potential to play a critical role in peace agreement enforcement. At present, however, it is prevented from fulfilling this potential due to controversies on the legal nature of peace agreements, and the limited number of available legal enforcement mechanisms. This article will address some of these controversies on the basis of a Colombian case study. Compared to other contemporary peace agreements, the Colombian peace agreement of 24 November 2016 with the FARC is detailed and comprehensive. It created a range of monitoring mechanisms, such as two UN political missions, a comprehensive follow-up commission ( CSIVI ), and an international observation mechanism. Despite the abundance of these monitoring mechanisms, gaps in protection remain. An analysis of the mechanisms shows that some peace agreement violations could not be adequately addressed by any of the available mechanisms—be it due to their political nature, or due to their limited mandates. Bearing in mind the relative sophistication of the Colombian peace agreement, this is reason for concern. The article aims to demonstrate the role that law could play in enforcing peace agreements, while also discussing persisting systemic shortcomings in the applicable legal framework.